Soccer in Action - Walker, Niki, 1972-; Dann, Sarah (New York : Crabtree Pub., 2000)
Introduces the techniques, equipment, rules, and safety requirements of soccer.
Includes index.
Keywords: Soccer -- Juvenile literature; Soccer